PENGETAHUANIBU TENTANGIMUNISASI DASAR LENGKAP MENUJU 100% UNIVERSAL CHILD IMMUNIZATION (UCI) DESA DI KECAMATAN PARIGI SELATAN - Nuraliah (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
One of the government's efforts to eradicate infectious diseases is by holding an immunization program with indicators of success, namely achieving Universal Child Immunization (UCI). The success of babies in getting the five types of basic immunization is measured through indicators of complete basic immunization as a basis for achieving international commitments, namely Universal Child Immunization (UCI). UCI sub-districts/villages are sub-districts/villages with complete basic immunization coverage for babies before 1 year old evenly throughout. Village/subdistrict. The aim of this research is to describe mothers' knowledge about complete basic immunization towards 100% Universal Child Immunization (UCI) in villages in South Parigi District. This type of research is descriptive research. The variable in this study is the mother's knowledge about complete basic immunization. The types of data in this research are primary data and secondary data. The analysis used in this research is univariate analysis. The population in this study were all mothers who had babies 0-12 months old in the working area of the Sumbersari Community Health Center, South Parigi District at the time the research was conducted. The sample was 43 people using an accidental sampling tech-nique. The results of this study showed that of the 43 respondents, 55.8% had good knowledge, 39.5% had sufficient knowledge and 4.7% had poor knowledge. The conclusion of this research is that mothers' knowledge of complete basic immunization towards 100% Universal Child Immunization (UCI) in villages in South Parigi District is mostly good